Compugirls : how girls of color find and define themselves in the digital age - Scott, Kimberly A. (Dissident feminisms., 2021)
"The heart of this book illuminates how, in the pursuit of dignity and hope, girls of color mediate and mitigate the digital and the social within their peer-directed space called COMPUGIRLS. COMPUGIRLS is a National Science Foundation-funded project-based, enrichment program for adolescent (ages 13 to 18) girls, and the program purposely targets girls from high needs schools who more frequently lack advanced computer science classes, opportunities for girls to become technological innovators, and teachers nurturing a context for student empowerment. Although often labeled as a technology program, COMPUGIRLS' core principles emphasize sociocultural elements such as identity (e.g. race, gender, ethnicity) interpersonal associations, and community advancement. I argue that through engagement and careful analysis of these constructs, girls will come to understand their intersubjectivities and reimagine their selves as agentic social actors with greater potential of becoming technologists. When girls reveal their selves and we analyze this process we learn which, how, and to what extent structures and systems contribute to their success in this digital age as well as the constraints preventing their liberation and participation in technological innovation. This book project provides the much-needed complexity to understanding how some girls of color find and define their selves in this digital age"--